Developing Card-Based Spinning Wheel Media via Team Game Tournaments to Enhance Student Learning Activities - Widiawati, Riesti; Setyowati, Dewi Liesnoor; Priyanto, Agustinus Sugeng (JESS (Journal of Educational Social Studies), 2025)
The learning process in the 21st century required students to develop critical thinking, collaboration, communication, and creativity skills, which must be supported by creative and innovative learning approaches and tools. This study aims to develop card-based spinning wheel media using the Teams Games Tournament (TGT) model, and to analyze the implementation of the media, students’ learning activities, and the practicality of the media. The media consisted of a physical spinning wheel equipped with six types of thematic question cards based on social studies aspects, namely: red cards (punishment), green cards (reward), yellow cards (economics), blue cards (history), purple cards (geography and civic education), and orange cards (sociology). This study employed a research and development (R&D) method using the ADDIE development model. During the media development process, the feasibility of the media was evaluated by content experts, media experts, and practitioners to ensure the quality and effectiveness of the developed product. The findings demonstrated that students’ learning activities on the topic of nationalistic values through the TGT model improved significantly. This was evidenced by classroom VIII students’ learning activity observation results, which reached 93.53% in the “very active” category. Student learning outcomes also met the minimum competency criteria, with an average score of 93.53%. Therefore, the findings indicated that the developement card-based spinning wheel media was both feasible and practical for use in social studies learning to enhance students’ learning activities.